(untitled) (Journal of the College of Basic Education, 2026)
This work explains the critical role of the differential equations systems in modeling and analyzing complex astronomical phenomena. The research demonstrates how these mathematical frameworks are fundamental to characterizing planetary motion, gravitational field dynamics, and orbital mechanics. Furthermore, it investigates the application of these systems to advanced astrophysical challenges, including satellite trajectory optimization, black hole dynamics, and galactic formation and evolution. The main finding of this research is that numerical methods and computational simulations are indispensable for solving these complex systems, enabling highly accurate predictions of celestial where analytical solutions are infeasible. The analysis confirms that techniques such as the Runge-Kutta methods are vital for applications in modern astronomy. The results emphasize that the integration of differential equations with advanced computational technology is a primary driver of progress in space exploration and astrophysical research. This synergy enhances our predictive capabilities for mission design, asteroid impact forecasting, and the understanding of gravitational interactions, thereby solidifying the indispensable link between mathematical theory and empirical astronomical discovery.